Collaboration in Multi-Partner R&D Projects: The Impact of Partnering Scale and Scope - Mishra, Anant; Chandrasekaran, Aravind; MacCormack, Alan (Journal of operations management, 2015)
How can firms design collaboration structures for effective performance in R&D projects that involve multiple partners? To address this question, we examine the theoretical underpinnings of collaboration structures in multi-partner R&D projects—i.e., the scale and the scope of partnering efforts. Partnering scale captures the extent of resource interdependencies between a firm and its partners; partnering scope captures both the breadth and depth of the interdependencies between a firm and its partners. Using primary data from 147 multi-partner R&D projects, we develop and test hypotheses that examine the impact of partnering scale and scope decisions on partnering performance. Results indicate that partnering scale has a curvilinear relationship with partnering performance. That is, intermediate levels of partnering scale are associated with higher partnering performance, compared to low or high levels of partnering scale. However, we also find that the nature of this relationship is moderated by the sub-dimensions of partnering scope. Specifically, increase in partnering breadth appears to magnify the negative effect of partnering scale on performance. In contrast, increase in partnering depth appears to overcome this negative effect, allowing firms to operate at higher levels of partnering scale. Taken together, these results highlight the importance of adopting a comprehensive approach to designing collaboration structures for multi-partner R&D projects.